Meta‐analysis of the association between body mass index and health‐related quality of life among adults, assessed by the SF‐3612. (16th April 2013) - Ul‐Haq, Zia; Mackay, Daniel F.; Fenwick, Elisabeth; Pell, Jill P.
Abstract Objective: Obesity is associated with impaired overall health‐related quality of life but individual studies suggest the relationship may differ for mental and physical quality of life. A systematic review using Medline, Embase, PsycINFO and ISI Web of Knowledge, and random effects meta‐analysis was undertaken. Design and Methods: Studies were included in the meta‐analysis if they were conducted on adults (defined as age >16 years), reported an overall physical and mental component score of the SF‐36, and, or both. Heterogeneity was assessed using I2 statistics and publication and small study biases using funnel plots and Egger's test. Between‐study heterogeneity was explored using meta‐regression. Results: Eight eligible studies provided 42 estimates of effect size, based on 43, 086 study participants. Adults with higher than normal body mass index had significantly reduced physical quality of life with a clear dose‐response relationship across all categories. Among class III obese adults, the score was reduced by 9.72 points (95% Confidence Interval 7.24, 12.20, P < 0.001). Mental quality of life was also significantly reduced among class III obese (−1.75, 95% confidence interval −3.33, −0.16, P = 0.031), but was not significantly different among obese (class I and class II) individuals, and was significantly increased among overweight adults (0.42, 95% confidence interval 0.17, 0.67, P = 0.001), compared to normal weight individuals. Heterogeneity was high in some categories, but there was no significant publication or small study bias. Conclusions: Different patterns were observed for physical and mental HRQoL, but both were impaired in obese individuals. This meta‐analysis provides further evidence on the impact of obesity on both aspects of health‐related quality of life.